FROM PROMPT TO POLITE: THE EFFICACY OF GENERATIVE AI IN FOSTERING DIGITAL PRAGMATIC COMPETENCE FOR ENGLISH REQUESTS AMONG PAKISTANI UNDERGRADUATES - Aftab Hussain; Dr. Ubaid Ullah Ubaid; Zakir Ali (International Premier Journal of Languages & Literature, 2025)
Pragmatic competence is crucial for digital communication, yet many Pakistani ESL undergraduates exhibit pragmatic failure in making requests due to traditional pedagogy. This paper investigates the efficacy of a generative AI (GenAI) intervention designed to foster this competence. A mixed-methods, quasi-experimental design was employed. Quantitative data from a pre and post-test Discourse Completion Task (DCT) were analyzed using paired and independent samples t-tests to measure changes in request strategies between an experimental and control group. Qualitative data from a questionnaire with open-ended and Likert-scale items captured learner perceptions. Results show the AI intervention led to a statistically significant improvement in the ability of the experimental group to modulate directness and use politeness markers. Thematic analysis revealed the AI tool, framed within a plurilingual pedagogy, enhanced confidence, reduced anxiety, and fostered critical metapragmatic awareness. This research offers a model for modernizing English curricula, demonstrating how technology can be used for critical linguistic inquiry and learner empowerment.